Implementación del protocolo global-gap 3.0 en mango de exportación con fines a certificación - López Aguilar, Carlos Luis (2012)
The cultivation of mango is consumed by an important and significant population, and in front of the requirement of the markets to national and international level to consume an innocuous and quality fruit, is precise that the producer know the alimentary security standards; It came into question in this context present it investigation Implementación of protocol globalgap 3,0 in mango of exportation with intentions to certification, at the farmstead Rapallo of property of the company Exofrut S.A, located the km 30 Road Playas, parish church Playas, it belongs to the canton Santa Elena of the province of Santa Elena, whose objectives matched : 1. Establishing the protocol's items Global Gap for the cultivation of mango; 2. Checking the fulfillment of the ground rules Global Gap at the farmstead Rapallo and 3. Decreeing the advantages than certification Global Gap offers it to the producer. The investigation started off with visitors to the estate following the implementation of protocol step by step, elaborating a scheme of the criteria of fulfillment and establishing specific points; Conferences of capacitation were given to the staff of farmstead, verifying the fulfillment of the good agricultural practices like a set of rules, determining the analysis of risks to identify the specific dangers and to establish measures for his control, taking the alimentary innocuousness into account, the adequate installations, equipments and utensils for the manipulation of foodstuff and hygiene in all the aspects of production and anthology. It came true with the beginnings of hygiene, examining the possible risks that present itself in all the productive space, assuring the health and labor certainty. 100 % of fulfillment in the bigger obligations was obtained and minors, that I assure the alimentary innocuousness of the mango. Himself I come to the conclusion that the fruit that is exported fulfills the standards of quality and worldwide hygiene, obtaining also a continuous improvement as to the internal processes at the estate.